Responses of the Ocular Anterior Segment and Refraction to 0.5% Tropicamide in Chinese School-Aged Children of Myopia, Emmetropia, and Hyperopia - Ying Yuan; Zhengwei Zhang; Jianfeng Zhu; Xiangui He; Ergang Du; Kelimu Jiang; Wenjing Zheng; Bilian Ke (Journal of Ophthalmology)
Purpose. To investigate the changes of anterior segment after cycloplegia and estimate the association of such changes with the changes of refraction in Chinese school-aged children of myopia, emmetropia, and hyperopia. Methods. 309 children were recruited and eligible subjects were assigned to three groups: hyperopia, emmetropia, or myopia. Cycloplegia was achieved with five cycles of 0.5% tropicamide. The Pentacam system was used to measure the parameters of interest before and after cycloplegia. Results. In the myopic group, the lenses were thinner and the lens position was significantly more posterior than that of the emmetropic and hyperopic groups in the cycloplegic status. The correlations between refraction and lens thickness (age adjusted; r=0.26, P<0.01), and lens position (age adjusted; r=-0.31, P<0.01) were found. After cycloplegia, ACD and ACV significantly increased, while ACA significantly decreased. Changes in refraction, ACD, ACV, and ACA were significantly different among the three groups (P<0.05, all). Changes of refraction were correlated with changes of ACD (r=0.41, P<0.01). Conclusions. Myopia presented thinner lenses and smaller changes of anterior segment and refraction after cycloplegia when compared to emmetropia and hyperopia. Changes of anterior chamber depth were correlated with refraction changes. This may contribute to a better understanding of the relationship between anterior segment and myopia.